MODEL PEMASARAN USAHA MIKRO KECIL DAN MENENGAH (UMKM) BERBASIS ONLINE DALAM MENDUKUNG PARIWISATA - Muhammad Tajuddin; Abdul Manan (Universitas Bumigora, 2017)
West Nusa Tenggara ’NTB’ is a region of the golden triangle stripe of tourism destination located between Komodo island and Tana Toraja. As the industry backing for small and middle scale businesses getting grow up and have got governmental supporting since economical crises hit Indonesia at the end 1997. In fact, many of those who have not yet optimize the information technology (IT) in running their business. The approach to meet the Small and Medium Enterprises (SMEs) with the proper customer or to find the proper raw material seller is through the media. Development of internet technology is so rapid, it is a necessity of SMEs using it as a business communications medium, because Internet utility for e-commerce complement has long been developed in both national and international scope. Furthermore, the research elaborates the integrated e-commerce model and SMEs as an information technology-based model of integrated marketing strategy besides, software creation and its implementation on SMEs in Mataram municipality. E-commerce and SMEs were designed to use System Development Life Cycle (SDLC) concerning the safety sistem, flowcart diagram and data base design aspects.